Numerical methods for determining the response in a dynamic mode - Филипский, Юрий Константинович; Фонарь, Людмила Сергеевна; Брянский, Андрей Эдуардович (Eastern-European Journal of Enterprise Technologies, 2013)
The transient processes lead to the fact that the calculations should be done in a dynamic state of the circuit. Therefore, the low-pass filter, functioning as integrator and used in most radio devices up to power supply units, should be analyzed in real time, i.e. in a dynamic mode. The method of transmission dynamic coefficient is of some interest, it differs from the stationary coefficient because it involves not only the instantaneous frequency value, but also the values of phase derivatives with respect to time. When determining the dynamic system output signal it is necessary to use z-conversion, allowing to eliminate the calculation errors which occur due to the limited frequency properties. Taking into account that the circuit remains in a dynamic mode for a long time, the calculation of passage of the limited sequence of rectangular pulses was carried out, spectral density at the circuit output was determined, z-image of the input signal and transmission coefficient were received, the signal at the circuit output was figured out. Using the z-conversion allows improving the accuracy of calculations and further determination of dynamic features of integrator. It can be concluded that, indeed, the circuit remains in dynamic mode for a long time. Each subsequent pulse at the circuit input causes the next stage, i.e. gradual voltage increase at the output